PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI LAJU REAKSI DI KELAS XI MIPA SMA NEGERI 1 BENAI - Jumarnis Jumarnis; Nofri Yuhelman; Rosa Murwindra (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
This study aims to determine the effect of the cooperative learning type snowball throwing model on student learning outcomes in the reaction rate material in class XI MIPA Benai 1 High School. The type of this research is quasi experiment withnonequivalent control group design research design. The population of this study is class XI MIPA Benai 1 Public High School Academic Year 2018/2019. Data collection techniques in this study were interviews, post-test and documentation. The final datawere analyzed using the Mann-Whitney U test. The results of data processing obtained the value of Sig. (2-tailed) = 0.005 ≤ α = 0.05. This proves that H0 is rejected, so it can be concluded that there are significant differences in student learning outcomes in the reaction rate material in class XI MIPA Benai 1 High School after the implementation of the snowball throwing type cooperative learning model. It can be seen from the average rating of each class namely the experimental class with an average of 41.29 and thecontrol class with an average of 28.10.